Assessment of fish health problems in freshwater aquaculture systems of Andhra Pradesh, India - Vineetha, P; Jawahar Abraham, T (Indian Journal of Fisheries, 2016)
Disease problems in carp culture systems in Andhra Pradesh and the measures taken by the farmers to combat diseases wereassessed. The major health problems encountered were argulosis, oxygen deficiency, hemorrhages and ulcerated red spots,myxoboliasis, gas bubble disease, gyrodactylosis, dropsy, lerneaosis, tail rot and stunted growth in Catla catla and Labeorohita. Argulosis has been a major cause of production loss, which occurred throughout the culture period. The use ofaquadrugs was found to be either unsuccessful or partially successful. Bacteria such as Acinetobacter, Aeromonas caviae,Aeromonas hydrophila, Pseudomonas spp. and members of Enterobacteriaceae were associated with diseased fish. Multipleantibiotic resistance was seen in 67% of the bacterial flora possibly due to antibiotic pressure in carp culture systems.